Analisis Kinerja Simpang Tak Bersinyal Jalan Temanggung Kanyapi – Jalan Wortel – Jalan Seth Adji Kota Palangka Raya - Olivia, Putri; Murniati; Robby (Jurnal Serambi Engineering, 2025)
The intersection of Temanggung Kanyapi Street, Wortel Street, and Seth Adji Street in Palangka Raya City is a frequent source of delays and congestion. This is due to the high volume of vehicles entering and exiting both main and minor roads. The situation is made worse by the dense activities around the intersection, such as residential areas, educational institutions, and commercial areas, which cause congestion during peak hours. This research will analyze the performance of the unsignalized intersection based on PKJI 2023 and provide recommendations for handling to improve intersection performance. Direct surveys are used to collect primary and secondary data, and key indicators such as Degree of Saturation (DS), Delay, and Queue Probability are calculated. The analysis results are clear: from Tuesday to Sunday, the DS value is ≤ 0.85, meaning the intersection is still operable. However, on Monday, the intersection's performance declines, with the DS value increasing to 0.93 (DS ≥ 0.85), indicating nearing saturation. The delay values range from 8.75 to 16.35 seconds per vehicle, with the largest delay occurring on Monday at 16.35 seconds per vehicle, which falls into category C.